NAFTA and the legalization of world politics : a case study - Abbott, Frederick M. (2000)
Analyzes the North American Free Trade Agreement (NAFTA) in the context of a broader project examining the causes and consequences of the legalization of world politics. Analyses and explains why trade negotiators have increasingly relied on hard law instruments to pursue international economic objectives and why a particular hard law model was used to create NAFTA.